2018
DOI: 10.4049/jimmunol.1701704
|View full text |Cite
|
Sign up to set email alerts
|

Development, Homeostasis, and Functions of Intestinal Intraepithelial Lymphocytes

Abstract: The intestine is continuously exposed to commensal microorganisms, food, and environmental agents and also serves as a major portal of entry for many pathogens. A critical defense mechanism against microbial invasion in the intestine is the single layer of epithelial cells that separates the gut lumen from the underlying tissues. The barrier function of the intestinal epithelium is supported by cells and soluble factors of the intestinal immune system. Chief among them are intestinal intraepithelial lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 151 publications
1
90
0
Order By: Relevance
“…They maintain epithelial integrity by promoting re-growth of healthy intestinal epithelial cells following cytolysis of epithelial cells during viral infection. They release interferon gamma (IFN-γ) and TNF-α as a response to an infection, which stimulate inflammation and intestinal barrier dysfunction [29,30].…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…They maintain epithelial integrity by promoting re-growth of healthy intestinal epithelial cells following cytolysis of epithelial cells during viral infection. They release interferon gamma (IFN-γ) and TNF-α as a response to an infection, which stimulate inflammation and intestinal barrier dysfunction [29,30].…”
Section: Adaptive Immunitymentioning
confidence: 99%
“… 12 , 13 Conversely, T-IEL are also cytotoxic cells that patrol the epithelial layer to sense and eliminate infected/damaged epithelial cells. 14 They are activated in response to oral infections with pathogens such as Salmonella, 15 , 16 Rotavirus, 17 and Toxoplasma gondii, 18 and at least in the context of loss of γδ T-IEL function, they appear to restrict pathogen entry. 15 , 16 , 19 , 20 Given their constant exposure to the gut microenvironment they must have the capacity to tolerate commensal bacteria while also being able to quickly recognize and fight enteric pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying gliadin‐mediated activation of the adaptive immune response are relatively well defined in CD, but the nature and regulation of the innate immune response within the epithelial compartment is not fully understood . Intraepithelial lymphocytes (IELs) constitute a diverse population, including thymus‐derived T cells of the αβ and γδ lineage and subsets of bone marrow‐derived innate lymphoid cells (ILCs) . It has been shown that IELs, specifically cytotoxic T cell receptor (TCR)‐αβ + T cells, which undergo natural killer (NK)‐like reprogramming on interacting with epithelial stress‐induced ligands, and IL‐15, up‐regulated upon exposure to toxic gliadin peptides, promote epithelial destruction .…”
Section: Introductionmentioning
confidence: 99%
“…Contributions of other types of lymphoid cells to the innate immune response in CD are suspected, but these are currently unclear . Recent studies have implicated ILCs in the pathogenesis of a variety of intestinal inflammatory disorders ; however, data regarding the repertoire of human proximal small intestinal (SI) ILCs and their alterations in CD are limited .…”
Section: Introductionmentioning
confidence: 99%